THE IMPACT OF INFLUENCER ENDORSEMENTS AND SOCIAL MEDIA ON CONSUMER BEHAVIOR AND BUSINESS STRATEGIES DECISION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Therefore, objectives of this study will investigate the effects of social media and social influence on the consumer's choice behavior and decision of the company. Due to the digital platform evolution of Instagram, TikTok, and YouTube, influencers continue to amass currency, as new influencers help shape consumer perceptions and purchase decisions. To understand how consumer, make choices using social media engagement or influencer recommendation, we research both primary and secondary sources. According to research, she or he thinks that when one of his or her consumer’s purchase decision is if one of that large segment of consumers think that influencer endorses and entertainment and connection is the reason why consumer’s social networks. An explanation of the business need influencer marketing in business strategy, business is more focused on social media than traditional marketing. However, it is necessary to explore future effects of this on consumer trust and loyalty. The results of this research illustrate the importance of businesses exploiting genuine influencer content to forge potentially tighter, as well as more competitive, ties with consumers in the ecosphere of the present.